Effects of microbial fermentation and microwave treatment on the composition, structural characteristics, and functional properties of modified okara dietary fiber. (April 2020) - Lin, Derong; Long, Xiaomei; Huang, Yichen; Yang, Yuanmeng; Wu, Zhijun; Chen, Hong; Zhang, Qing; Wu, Dingtao; Qin, Wen; Tu, Zongcai
Abstract: The effects of mixed fermentation by lactic acid bacteria and Neurospora crassa, and microwave treatment on the composition, structure, and functional properties of okara dietary fiber (DF) were studied. The results of SEM and EDX showed that the honeycomb structure was more obvious and the content of elemental components was changed after fermentation and microwave treatment. The result of TGA-DSC showed that the thermal stability of the sample improved following microwave treatment. The FT-IR results showed that fermentation and microwave treatment effect the functional groups of cellulose and hemicellulose in a manner consistent with the composition of the samples, and the crystal structures of the samples were slightly damaged after modification. There was no obvious change in the adsorption effect of cholesterol and sodium cholate following mixed fermentation and microwave treatment. However, the inhibition ratio of fermented DF on α-amylase activity increased from 9.55% to 15.04%, while that of microwave-treated DF changed from 9.55% to 20.92%. The glucose dialysis retardation of fermented DF doubled at 30 min. Overall, both methods improve the availability of DF in okara. Modified DF from okara can be used as a functional ingredient in diverse food products. Highlights: The SDF was prepared by the mixed fermentation and microwave treatment. The composition and structural characteristics of UFDF, FDF and MDF were compared. The functional properties of UFDF, FDF and MDF were compared. The modification mechanisms of mixed fermentation and microwave treatment were discussed preliminarily.